PERAN KEPOLISIAN RESORT KUTAI KARTANEGARA DALAM PENANGANAN KASUS RUNTUHNYA JEMBATAN KUTAI KARTANEGARA BERDASARKAN KITAB UNDANG – UNDANG HUKUM ACARA PIDANA (KUHAP) - Vita Marinda Noor (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT Lifting this title is an interesting thing for authors, because of these events appear caused some speculation about the case of Kutai bridge collapse, Crime referring to allegations of corruption to the “Deliberate element”, or pure negligence that caused the workers and the person in charge in the process of maintenance, so the author want to know how exactly this event so the author lifted the title about Role of Kutai Kartanegara Police in Handling Cases of Kutai Kutai Bridge Collapse of Criminal Procedure.The research method in this thesis include the type of research that uses methods of empirical jurisdiction, primary and secondary data sources, the study site in Kutai Police and Department of Public Works , data collection techniques such as literature studies and field studies that include observation, interviews, and documentation.The purpose of this study was to determine the duties and authority of the police in handling the case of the collapse of Kutai bridge as well as for knowing what are the barriers to the investigator in charge of the case and to add the treasures of knowledge for the entire academic community of the University of Samarinda August 17, 1945 lastly.Results showed that : Kutai Police have carried out duties and responsibilities pursuant to Article 6, Article 7, Article 8 and Article 9 of Law No. 2 of 2002 on the Indonesian police in the event of the collapse of Kutai Bridge next to the investigation process by Investigator Police aquatic mammal has been in accordance with the Law - Criminal Procedure Code is reinforced in Article 16 and in the process until the beginning of the title Determination Case Suspect, Police encountered some obstacles such as case investigation activities Article 359 of the Criminal Code in conjunction with Article 360 of the Criminal Code.The author hopes of incident events Kutai Bridge Collapse of the Government and the Company is the winning bidder over do a better planning until the implementation of the maintenance of this bridge, in order to avoid further accidents which caused loss of human life, and I appreciate the performance of the police who have successfully set the suspects in the event of collapse of the Kutai Kartanegara Bridge. Keywords: Investigators, Duties and Powers of Police, Bridge Construction